The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.biochem.0c00961
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of a 26 kDa Protein by Cryo-Electron Microscopy Aided by a Small Scaffold Protein

Abstract: Cryo-electron microscopy (cryo-EM)-based structure determination of small proteins is hindered by the technical challenges associated with low signal-to-noise ratios of their particle images in intrinsically noisy micrographs. One solution is to attach the target protein to a large protein scaffold to increase its apparent size and, therefore, image contrast. Here we report a novel scaffold design based on a trimeric helical protein, E. coli ornithine transcarbamylase (OTC), fused to human ubiquitin. As a proo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Its interaction is structurally well characterized with the Ub-bound structure having been solved by both X-ray crystallography and cryo-electron microscopy (CryoEM). [28,40] Our Ub T9Bpa crosslinking results show that there is one equivalent of Ub binding as suggested by SDS-PAGE gel. Photocrosslinking reaction mixtures were subjected to tryptic digestion and analysis by LC-MS/MS.…”
Section: Resultssupporting
confidence: 61%
“…Its interaction is structurally well characterized with the Ub-bound structure having been solved by both X-ray crystallography and cryo-electron microscopy (CryoEM). [28,40] Our Ub T9Bpa crosslinking results show that there is one equivalent of Ub binding as suggested by SDS-PAGE gel. Photocrosslinking reaction mixtures were subjected to tryptic digestion and analysis by LC-MS/MS.…”
Section: Resultssupporting
confidence: 61%
“…Soluble expression and purification will be crucial for structural characterization via CD, NMR, and Cryo-EM. Due to their small size and high disorder content, only NMR 25 and potentially Cryo-EM 64 will be capable of solving the structure of de novo proteins experimentally. Even in light of the recent dawn of computational structure prediction, 65,66 experimental structural and functional determination remains necessary, especially for de novo proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions. While cryoEM structures of molecules smaller that 100 kDa in size are available [25][26][27][28]31 they have been often the results of a one-off process that tested the current technology and software, or obtained by extensive manipulation of the sample itself 26,[47][48][49] but did not address the need for reproducibility in structure determination, as well as the necessity of identifying ligands bound, two essential requirement for the use of cryoEM derived information in drug discovery and development. In this paper we have shown that routine structural determination of molecules less than 70 kDa in size is possible, and that visualization of bound ligands is achievable.…”
Section: Resultsmentioning
confidence: 99%